2019
DOI: 10.1039/c8fo02450b
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from chicken processing by-product inhibit DPP-IV and promote cellular glucose uptake: potential ingredients for T2D management

Abstract: A low molecular weight peptide fraction from chicken by-product hydrolysate was found to inhibit DPP-IV in vitro and promote cellular glucose uptake ex vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Type 2 diabetes is the most prevalent form, accounting for approximately 90% of cases [1]. Type 2 diabetes is characterized by insufficient pancreatic insulin secretion and/or insulin resistance in peripheral tissues, and is associated with various complications such as retinopathy, nephropathy and neuropathy, thus resulting in serious harm to human health [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes is the most prevalent form, accounting for approximately 90% of cases [1]. Type 2 diabetes is characterized by insufficient pancreatic insulin secretion and/or insulin resistance in peripheral tissues, and is associated with various complications such as retinopathy, nephropathy and neuropathy, thus resulting in serious harm to human health [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Dipeptides as X-Pro with X as a small size hydrophobic amino acid would likely be an effective inhibitor. Presence of hydrophobic and aromatic amino acids at N-terminal end of peptides with DPP-IV inhibitory activity was also reported by Lima et al [65]. Ren et al [63] evaluated the α-glucosidase inhibitory capacity of peptides from hemp seed and indicated that hydrophobicity of peptides was a prime factor affecting inhibitory activity and molecular weight as a second priority.…”
Section: In Vivo In Vitromentioning
confidence: 53%
“…Moreover, the regular intake of this particular dry-cured ham did not disturb the metabolic profile of the CV patient; in fact, a trend to decrease the glycemic profile and improve the lipid profile was found. The actions that bioactive peptides play on the glycemic profile are currently under investigation [38], and a possible dipeptidyl peptidase-IV and α-glucosidase inhibition or at the level of glucose intake had been suggested [39][40][41]. Regarding the lipid metabolism, the consumption of dry-cured ham could interfere at the digestive level with the absorption of bile salts rich in cholesterol, acting as a sequestrant of bile salts, an action like that exerted by resins [42].…”
Section: Key Metabolic Pathwaysmentioning
confidence: 99%